NEUROENDOCRINE TUMORS OF THE PITUITARY GLAND – MODERN DIAGNOSTIC APPROACH - Mihajlović, Milena; Manojlović Gačić, Emilija (Medicinski podmladak, 2023)
Pituitary neuroendocrine tumors (PitNET) are neuroendocrine tumors originating from adenohypophyseal cells. Although benign, PitNETs sometimes exhibit aggressive biological behavior that was the inspiration for the change of old and traditional name “pituitary adenomas”. Current standard in PitNET diagnostics according to WHO criteria is immunohistochemistry, with application of antibodies to adenohypophysis hormones and transcription factors TPIT (T-box family member TBX19), PIT1 (pituitary transcription factor 1) and SF-1 (steroidogenic factor-1) according to which, the line of differentiation is assessed. In the PIT1 line of differentiation there are somatotroph, lactotroph and thyrotroph tumors. Somatotroph tumors are from PIT1 lineage that produce growth hormone (GH). The WHO defines the following subtypes of somatotroph tumors: densely granulated and sparsely granulated somatotroph tumor. Lactotroph tumors are the most common neuroendocrine tumors of the pituitary gland. The transcription factors PIT1 and the estrogen erceptor α (ERα) play a key role in their genesis. There are two subtypes of lactotroph tumors, densely and sparsely granulated that are differentiated by the type of prolactine (PRL) staining pattern. Thyrotroph tumors expess both PIT1 and GATA binding protein 3 (GATA3), and can show variable positivity for thyroid-stimulating hormone (TSH). Beside these three main tumor types of PIT1 lineage, there are mixed lactotroph and somatotroph tumors, mamosomatotroph tumor, acifophilic “stem cell” tumor, mature and immature plurihormonal tumor. Corticotroph tumors express transcription factor TPIT, and produce adrenocorticotrophic hormone (ACTH). They can be densely granulated and sparsely granulated. Rare subtype of corticotroph tumors, that can show aggressive biological behavior, is crooke cell tumor. Gonadotroph tumors are of SF1 lineage of differentiation, and they produce follicle-stimulating hormone (FSH) and luteinizing hormone (LH). Null-cell tumors show no distinct cell lineage, and do not express any of the transcription factors. With the use of transcription factors, these tumors are diagnosed through elimination, and their number tented to decrease.